Assessment of disease activity and progression in Takayasu's arteritis with Disease Extent Index-Takayasu - DİRESKENELİ, RAFİ HANER (OXFORD UNIV PRESS, 2010)
Objective. Disease Extent Index-Takayasu (DEI.Tak) is a new index developed for the follow-up of Takayasu's arteritis ( TA), assessing only clinical findings without the requirement of imaging. We investigated the effectiveness of DEI.Tak in assessing disease activity and progression by comparing with physician's global assessment ( PGA) and active disease criteria defined by Kerr et al. Methods. The initial DEI.Tak forms were filled in for 145 TA patients cross-sectionally to detect the baseline damage and after 29.8 (31) months (n = 105, 144 visits) only by including the new/worsening symptoms within the past 6 months. Results. At baseline, all patients had a DEI.Tak > 0 [mean (s.d.): 7.6 (4.2)]. At this evaluation, 62% of the patients had active, 16.2% had persistent and 21.8% had inactive disease according to the PGA. At follow-up, in 69% of the patients the DEI.Tak score was 0. However, 14% of them were accepted as having active and 17% persistent disease according to PGA. In contrast, 18% with a DEI.Tak epsilon 1 were inactive according to PGA. Patients with active or persistent disease with PGA had higher DEI.Tak compared with inactives [1.3 (1.9), 1 (1.3) vs 0.2 (0.6), respectively; P < 0.001]. According to Kerr's criteria 27% were active. The total agreement between DEI.Tak and Kerr's criteria was 94% (kappa = 0.85). Compared with PGA, Kerr's criteria had a total agreement of 74% and DEI.Tak 68%. Conclusion. During follow-up, most TA patients showed no clinical activity with DEI-Tak. Although the agreement between Kerr's criteria and DEI.Tak seemed very good, using Kerr's criteria instead of DEI.Tak increased the consistency with PGA, which could be explained by the influence of imaging data and acute-phase reactant levels on the physician's decisions.
Keywords: Takayasu arteritis; Disease activity; DEI; Tak; Birmingham vasculitis activity score; LIMITATIONS; THERAPY